2012
DOI: 10.3382/ps.2011-01990
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Pit-1 gene and its association with growth traits in chicken

Abstract: The Pit-1 gene is involved in regulation of muscle growth through controlling the expression of growth hormone, prolactin, and transforming growth factor-β genes in chicken. The objectives of the study were to explore polymorphisms of the Pit-1 gene and to estimate the effect of these polymorphisms on growth traits in PB-1 and control (broiler strain) and IWI (layer strain) chickens. Single-stranded conformation polymorphism followed by sequencing was performed to reveal polymorphisms of the gene. In total, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…Earlier studies also revealed that the differential level of expression of MSTN gene may be attributed to variability in sequence of the promoter region (Gu et al 2004;Du et al 2005). A similar type of substitution was also observed by Bhattacharya et al 2012) in the promoter region of the Pit1 gene in poultry. In order to study the effect of these mutations on MSTN gene regulation, MSTN promoter sequence was analyzed in silico for the presence of putative transcription factor binding sites at SNPs.…”
Section: Point Mutation At the Mstn Promoter Overlaps With The Transcmentioning
confidence: 70%
“…Earlier studies also revealed that the differential level of expression of MSTN gene may be attributed to variability in sequence of the promoter region (Gu et al 2004;Du et al 2005). A similar type of substitution was also observed by Bhattacharya et al 2012) in the promoter region of the Pit1 gene in poultry. In order to study the effect of these mutations on MSTN gene regulation, MSTN promoter sequence was analyzed in silico for the presence of putative transcription factor binding sites at SNPs.…”
Section: Point Mutation At the Mstn Promoter Overlaps With The Transcmentioning
confidence: 70%
“…A 12% native PAGE (50:1, acrylamide and bisacrylamide) with 5% glycerol was prepared to resolve the SSCP pattern following a standard protocol (Bhattacharya et al, 2012). A volume of 3 µl PCR product mixed with 15 µl formamide dye (95% formamide, 0.025% xylene cyanol, 0.025% bromophenol blue, 0.5 M EDTA) was denatured at 95°C for 5 min followed by snap cooling on ice for 15 min.…”
Section: Pcr Single-stranded Conformation Polymorphism and Sequencingmentioning
confidence: 99%
“…A volume of 50 μl blood was collected aseptically from the wing vein. Genomic DNA was isolated from blood cells following a standard protocol (Bhattacharya et al, 2012). The quality of DNA was verified by 0.8% agarose gel electrophoresis while quantity was checked by spectrophotometer.…”
Section: Sample Collection and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…A pair of primers were used for amplification of GAPDH gene, which was as an internal control. The amplification and analysis was performed according standard protocol [18].…”
Section: Realtime-pcrmentioning
confidence: 99%